2021
DOI: 10.3390/su131911112
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Challenges and Strategies in Land Productivity in Sikkim Himalaya, India

Abstract: Agriculture is the major source of livelihood in rural areas and is considered the backbone of the Indian economy. In Sikkim, agriculture is being practiced by 80% of the rural population, and having no other major livelihood options has created immense pressure on the farmers and agricultural land. Agriculture sector is under great stress as the farmers are being confronted by various challenges in Sikkim Himalaya in recent years, such as land degradation, climate change and socio-economic problems. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In all of these villages, the majority of households still practice mixed farming, with mostly subsistence crops and a herd of cows and goats. The majority of the households reported that soils were becoming less productive and had lost much of their previous production capability [39]. Maize, paddy, ginger, vegetables, and cardamom are still the main crops, among which paddy, ginger and vegetables require manure.…”
Section: Characteristics Of Respondents and Sample Villagesmentioning
confidence: 99%
“…In all of these villages, the majority of households still practice mixed farming, with mostly subsistence crops and a herd of cows and goats. The majority of the households reported that soils were becoming less productive and had lost much of their previous production capability [39]. Maize, paddy, ginger, vegetables, and cardamom are still the main crops, among which paddy, ginger and vegetables require manure.…”
Section: Characteristics Of Respondents and Sample Villagesmentioning
confidence: 99%
“…Agriculture and related activities play a significant role in the lives of the Himalayan economy. A majority of these activities are centred between 1200 and 2000 m above sea level (mid-hill zone), where agriculture and allied activities account for about 80% of the rural economy [1,2]. The region differs in terms of topography, cropping patterns, agricultural practices, and in many more ways.…”
Section: Introductionmentioning
confidence: 99%
“…The region differs in terms of topography, cropping patterns, agricultural practices, and in many more ways. Traditional agricultural practices depend heavily on forest-derived resources (vegetative materials such as fodder and bedding leaves, and animal wastes) and are prominently subsistence-based without any commercial interest [2][3][4]. Production is meagre as the area under arable land is extremely limited and fragmented, with poor irrigation facilities [4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to hilly and difficult terrain, expansion of area under cultivation is limited and per-capita availability of land is low. Dependence of majority of the population and small holdings has kept agriculture at subsistence levels (Mishra et al, 2021). Traditional production technology, lack of reliable marketing channels, presence of large number of intermediaries, poor infrastructure support and vulnerability to natural calamities are the major constraints faced by smallholder farmers in the state (Subba, 2014;Sharma et al, 2017;Gurung, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to hilly and difficult terrain, expansion of area under cultivation is limited and per-capita availability of land is low. Dependence of majority of the population and small holdings has kept agriculture at subsistence levels (Mishra et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%